Jack and the Beanstalk - Anna Milbourne (England Usborne Publishing, 2023)
This beautifully illustrated picture book retells the story of Jack and his mother who are so poor, they have no food and not much hope... until Jack meets a strange little man with a handful of magic beans.
Keywords: EY - RM -- EY - RM